Screening new enzymes for enzymatic deinking - Marques, Susana (2001)
[Excerpt] Introduction: The deinking process involves the ink particles dislodgement from the fibre surface and the separation of the dispersed ink. The use of enzymes is generally related either to the fibre surface or the ink particles attack (I ,2 ,3 ,4 ). For that matter, enzymatic deinking is known to greatly depend on the pulp characteristics, namely the chemical composition of the fibre and ink particles and the printing process involved, which defines the fibre/ink interactions. Additionally, other variables influence the process (consistency, pH, temperature, mixing), which cannot be ignored (3,5,6,7). In the present work several xylanolytic and cellulolytic enzymes with potential affinity to fibre constitutive were produced and preliminary characterised so that their contribution to the deinking of a mixed office wastepaper sample could be evaluated. [...]